Performance Appraisal Techniques And Their Effects On Organizational Growth - Ifeanyi Martins NWOKEOCHA, PhD (International journal of technology and education research, 2024)
Employee performance appraisal is a focal aspect of human resources management. It analyzes employees’ performance and ensures that employees perform at the desired level to achieve organizational objectives. This paper examined issues of performance appraisal and their effects on organizational growth in. The paper adopted a qualitative research method. It depended on secondary data from scholarly journals and equity and goal setting theory as a framework of analysis. The study oserved that performance appraisal does not only promote organizational performance but provides potency in determining employee capacity, skills acquisition, and experience for organizational growth. The paper concluded that organizations which tend to be effective are positively engaged in continuous appraisal of employee performance in order to correct deviance and enhance better performance in the organization. The study recommended that the management of organizations should create an enabling environment and opportunities for self-appraisal or self-evaluation. The management of organizations should ensure that the number of workers being evaluated by a rater should not be too large, so that he can have enough time to do a thorough job on each person.